The Alarming Prevalence of Cardiovascular Risk Factors among the Undergraduate Medical Students in Bangladesh - Khan, Moniruzzaman; Satabdi Ghosh; A K M Shahidur Rahman; Md Raihan Talukder; Wakif Khan; Kapil Dev Sarker; Munmun Ghosh (KYAMC Journal, 2023)
Background: Cardiovascular disease (CVD) is a major emerging health problem. In Bangladesh, 27% of death occur due to CVD. Due to limited physical activity and dietary changes are the most common cause for higher incidence of CVD in developing countries. Overweight and obesity also affects. So, among young adults, the prevalence of CVD risk factors need to be assessed urgently. Objective: To assess the prevalence of risk factors of cardiovascular disease in undergraduate medical students. Materials and Methods: A cross-sectional study, among 4th year medical students was done in the Department of Pharmacology and Therapeutics, Khwaja Yunus Ali Medical College (KYAMC) from September 2022 to November 2022. The 4th year 90 medical students (40 male & 50 female) were included in this study. A questionnaire form containing sociodemographic criteria was provided to them. The physical parameter like systolic blood pressure, diastolic blood pressure, height, weight and waist circumference also were recorded. From these results Body Mass Index and waist-height ratio were calculated. Results: Our result showed that 25% of male and 36% of female medical students were overweight and obesity was more among male medical students (12.5%) than female(2%). 62.5% male and 78% female medical students were physically inactive. Conclusion: Changing the life style, eating habit and physical inactivities in early adulthood increases the risk of cardiovascular disease. The present study revealed the higher proportion of female students being overweight, physically inactive and more familial predisposition for developing CVD. KYAMC Journal Vol. 14, No. 02, July 2023: 87-91.